Intimate partner violence during pregnancy and its association with birth asphyxia in hospitals of Tigray region, Ethiopia - Kahsay Zenebe Gebreslasie; Gelawdiwos Gebre; Dawit Zenebe; Rahel Nardos; Aklil Birhane (BMC, 2024)
Abstract Background Birth asphyxia is the main cause of neonatal mortality and morbidity worldwide. Some studies indicate intimate partner violence during pregnancy is a risk factor for birth asphyxia. In Ethiopia, intimate partner violence during pregnancy is reported to be high. Despite this high prevalence, there is a lack of data about the association of birth asphyxia and intimate partner violence. The aim of this study was to assess the prevalence of intimate partner violence during pregnancy and its associated factors with birth asphyxia in health facilities in the Tigray region of northern Ethiopia. Methods This was an institutional-based cross-sectional study conducted at select health facilities in the Tigray region of Ethiopia. Random sampling technique was employed to select health facilities and systematic sampling was used to select 648 study participants. Data was entered by using Epi info version 3.5.1 and was analyzed using SPSS version 20. Bivariate and multivariate analysis was done to assess the association between exposure to intimate partner violence during pregnancy and birth asphyxia after adjusting for possible confounders. Results The prevalence of intimate partner violence during pregnancy was 47(7.3%). Eighty two (12.7%) babies were delivered with birth asphyxia. Intimate partner violence during pregnancy had a significant association with birth asphyxia, AOR (95% CI) = 4.4(2-9.8). In addition to this, other factors that were associated with birth asphyxia include place of residence [ AOR (95% CI) = 2.7(1.55-4.8)], age > 19 [AOR (95% CI) = 2.9(1.29-6.5)], age 20-35 [AOR (95% CI) = 3.1(1.06-9.3)], gestational age < 37 weeks [AOR(95% CI) = 7.2(3.5-14.8)] and low birth weight [AOR(95% CI) = 3.9(2.1-7.3)]. Conclusions The prevalence of birth asphyxia in this study is high and is further increased by intimate partner violence during pregnancy. Health care providers and policy makers should take measures aimed at preventing intimate partner violence during pregnancy to reduce harm to the mother and adverse birth outcomes.